O cinema Disney agente da história: a cultura nas relações internacionais entre Estados Unidos, Brasil e Argentina (1942-1945) - Ferreira, Alexandre Maccari (2008)
To conceive a movie as a document and as a historic tool is important nowadays, when images are considered fundamental in the acceptance and reception of specific purposes in the teaching level or in people s everyday lives. This dissertation intends to study the representative connections of the American approach policies in the 40 s through a cinematographic perspective, especially through the Disney movies Saludos, amigos! (1942) and The three caballeros (1945). These movies highlight some aspects of the Argentinean and Brazilian history, as well as of some other Latin-American countries, revealing the American impressions about South American countries and Mexico during World War II. This period featured the approximation of the North American and Latin American politics. This dissertation intends to provide a critical analysis of the historical and political fields in relation to the cultural and cinematographic universes, highlighting their closeness and detachments, taking in consideration the theoretic studies that relate the movies as an advertisement tool, spreader of ideologies, of moral codes, of philosophical divagations and of political propositions that would result in the spectator s acceptance and abidance.